Short communicationChronic total occlusion successfully treated with a bioresorbable everolimus-eluting vascular scaffold - Rama-Merchan, Juan Carlos; Mattesini, Alessio; Dall’Ara, Gianni; Di Mario, Carlo (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Fully bioresorbable vascular scaffolds (BVS) are a new approach to the percutaneous treatment of coronary artery disease. The BVS have not yet been fully tested in complex lesions, including chronic total occlusion (CTO). We report a CTO case successfully treated with a second-generation bioabsorbable drug-eluting scaffold.